2016
DOI: 10.1146/annurev-fluid-122414-034314
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Mechanics of Heart Valves and Their Replacements

Abstract: As the pulsatile cardiac blood flow drives the heart valve leaflets to open and close, the flow in the vicinity of the valve resembles a pulsed jet through a nonaxisymmetric orifice with a dynamically changing area. As a result, three-dimensional vortex rings with intricate topology emerge that interact with the complex cardiac anatomy and give rise to shear layers, regions of recirculation, and flow instabilities that could ultimately lead to transition to turbulence. Such complex flow patterns, which are inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 146 publications
6
91
0
Order By: Relevance
“…During the cardiac cycle, blood exerts a continuous loading on the aortic valve, which experiences compression, stretching, and bending stresses . Conversely, the interaction of the pulsatile blood flow with the valve flexible leaflets gives rise to complex flow structures in the vicinity of the valve, which could eventually lead to transition to turbulence . Assessing these complex structural and flow features could not only ultimately allow to improve the understanding of the degeneration process leading to aortic valve calcification but also drastically help the design of aortic valve prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…During the cardiac cycle, blood exerts a continuous loading on the aortic valve, which experiences compression, stretching, and bending stresses . Conversely, the interaction of the pulsatile blood flow with the valve flexible leaflets gives rise to complex flow structures in the vicinity of the valve, which could eventually lead to transition to turbulence . Assessing these complex structural and flow features could not only ultimately allow to improve the understanding of the degeneration process leading to aortic valve calcification but also drastically help the design of aortic valve prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, dissipation is likely associated with the complex vorticity structures seen downstream of the valve. These structures are described in more detail elsewhere 25, 76, 87 . Other methods involving passive flow control may alter these structures and could be combined with SH technology to improve performance 12, 26, 31, 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Shear stress can also directly stimulate platelet activation in the absence of hemolysis, further promoting thrombo-embolic complications 1, 3, 8, 9, 38 . As a result of these risks, many studies have attempted to characterize shear stress and Reynolds shear stress (RSS) in MHVs through experimental and computational fluid dynamics 25, 34, 55, 76, 87 . Sotiropoulos et al provides a review of these dynamics and an explanation for how RSS can contribute to hemolysis or platelet activation by impacting the instantaneous shear stress experienced by blood cells is further explored in Morshed et al 59, 76 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the well-established tri-leaflet design has been clinically proven to have long term durability [2] and low levels of thromboembolism [3], recent studies have suggested that the implantation of an artificial valve at the mitral position can significantly alter left ventricle flow field [4][5][6], as various parameters including valve geometry and orientation can have an effect on hemodynamics [7].…”
Section: Introductionmentioning
confidence: 99%